Study of temperature classification, spark ignition and drop test assessment on secondary cells for intrinsically safe equipment for explosive atmospheres. Issue 4 (29th April 2019) - Ahirwal, Bhagirath; Vishwakarma, Rajendra K.
Abstract: In any explosive atmosphere the cell/battery (pack of secondary cells) is used in handheld intrinsically safe (IS) apparatus. The cell is a rechargeable battery. Chemically similar cells of different makes were assessed for maximum surface temperature followed by the spark ignition test as per IS/IEC 60079‐11. It was observed that the maximum surface temperature, open voltage, and short circuit current varied among cells having the same maker and nominal capacity. The cells were not vented or leaked or exploded during the short circuit test for determining the temperature class of cells. The cells with protection circuit had passed in spark ignition test but failed without protection circuit. It may be recommended that the cell should not be used without appropriate protection circuit even in a low power rating certified IS circuit for hazardous areas. A study was also carried out for spark ignition test on different cells connected to the IS protection circuit and the certified IS apparatus as a composite circuit. Each cell was encapsulated along with IS protection circuit and endured drop test successfully. This study was revealed that cell(s) may be used with appropriate IS protection circuit for IS apparatus/equipment.